The influence of squat depth on maximal vertical jump performance - Domire, Z. J.; Challis, J. H. (Journal of Sports Sciences, 2007)
An increase in the period over which a muscle generates force can lead to the generation of greater force and, therefore, for example in jumping, to greater jump height. The aim of this study was to examine the effect of squat depth on maximum vertical jump performance. We hypothesized that jump height would increase with increasing depth of squat due to the greater time available for the generation of muscular force. Ten participants performed jumps from preferred and deep squat positions. A computer model simulated jumps from the different starting postures. The participants showed no difference in jump height in jumps from deep and preferred positions. Simulated jumps produced similar kinematics to the participants' jumps. The optimal squat depth for the simulated jumps was the lowest position the model was able to jump from. Because jumping from a deep squat is rarely practised, it is unlikely that these jumps were optimally coordinated by the participants. Differences in experimental vertical ground reaction force patterns also suggest that jumps from a deep squat are not optimally coordinated. These results suggest there is the potential for athletes to increase jump performance by exploiting a greater range of motion.